Inelastic x-ray scattering from shocked liquid deuterium. - Regan, S; Falk, K; Gregori, G; Radha, P; Hu, S; Boehly, T; Crowley, B; Glenzer, S; Landen, O; Gericke, DO; Döppner, T; Meyerhofer, D; et al. (2012)
The Fermi-degenerate plasma conditions created in liquid deuterium by a laser-ablation-driven shock wave were probed with noncollective, spectrally resolved, inelastic x-ray Thomson scattering employing Cl Ly(α) line emission at 2.96 keV. These first x-ray Thomson scattering measurements of the microscopic properties of shocked deuterium show an inferred spatially averaged electron temperature of 8±5  eV, an electron density of 2.2(±0.5)×10(23)  cm(-3), and an ionization of 0.8 (-0.25, +0.15). Two-dimensional hydrodynamic simulations using equation-of-state models suited for the extreme parameters occurring in inertial confinement fusion research and planetary interiors are consistent with the experimental results.